Differential IL‐1 signaling induced by BMPR2 deficiency drives pulmonary vascular remodeling. (1st September 2017) - Pickworth, Josephine; Rothman, Alexander; Iremonger, James; Casbolt, Helen; Hopkinson, Kay; Hickey, Peter M.; Gladson, Santhi; Shay, Sheila; Morrell, Nicholas W.; Francis, Sheila E.; West, James D.; Lawrie, Allan
Abstract : Bone morphogenetic protein receptor type 2 (BMPR2) mutations are present in patients with heritable and idiopathic pulmonary arterial hypertension (PAH). Circulating levels of interleukin‐1 (IL‐1) are raised in patients and animal models. Whether interplay between BMP and IL‐1 signaling can explain the local manifestation of PAH in the lung remains unclear. Cell culture, siRNA, and mRNA microarray analysis of RNA isolated from human pulmonary artery (PASMC) and aortic (AoSMC) smooth muscle cells were used. R899X +/– BMPR2 transgenic mice fed a Western diet for six weeks were given daily injections of IL‐1ß prior to assessment for PAH and tissue collection. PASMC have reduced inflammatory activation in response to IL‐1ß compared with AoSMCs; however, PASMC with reduced BMPR2 demonstrated an exaggerated response. Mice treated with IL‐1ß had higher white blood cell counts and significantly raised serum protein levels of IL‐6 and osteoprotegerin (OPG) plasma levels recapitulating in vitro data. Phenotypically, IL‐1ß treated mice demonstrated increased pulmonary vascular remodeling. IL‐1ß induces an exaggerated pulmonary artery specific transcriptomic inflammatory response when BMPR2 signaling is reduced.